2020
DOI: 10.1016/j.omtn.2020.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Circulating miR-194-5p Reverses Osteoporosis through Wnt5a/β-Catenin-Dependent Induction of Osteogenic Differentiation

Abstract: Mesenchymal stem cells (MSCs) critically contribute to bone formation, and proper induction of osteogenic differentiation can lead to an increase in bone mass. In the present study, we reported that an increased miR-194-5p level in plasma is inversely related to the degree of bone formation in osteoporosis patients. We also noted that increased miR-194-5p in the MSCs of ovariectomized (OVX) mice and agomiR-194-5p manipulation of miR-194-5p significantly suppressed bone formation, both in aged and OVX mice. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, Mi et al [ 62 ] reported that miR-194-5p is upregulated in the plasma samples from osteoporosis patients, which is inversely associated with the degree of bone formation in these affected individuals. Subsequently, it was detected that this miRNA inhibits osteoblast differentiation and diminishes bone mass in vivo and impedes osteogenic differentiation in vitro.…”
Section: Osteoporosis and Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Mi et al [ 62 ] reported that miR-194-5p is upregulated in the plasma samples from osteoporosis patients, which is inversely associated with the degree of bone formation in these affected individuals. Subsequently, it was detected that this miRNA inhibits osteoblast differentiation and diminishes bone mass in vivo and impedes osteogenic differentiation in vitro.…”
Section: Osteoporosis and Mirnasmentioning
confidence: 99%
“…Besides, it was found that the target of miR-194-5p is the Wnt-5a protein (WNT5A), whose main function is related to the induction of osteogenic differentiation through the Wnt5a/β-catenin signaling pathway. Accordingly, the increased expression of miR-194-5p during osteoporosis affects osteogenic differentiation and aggravates bone loss via targeting Wnt5a [ 62 ]. In addition, it has been stated that frizzled-4 (FZD4), a protein associated with osteogenic differentiation, is a potential target of miR-1286.…”
Section: Osteoporosis and Mirnasmentioning
confidence: 99%
“…Comparison between osteoporotic patients and controls [ 16 , 20 , 22 , 24 , 27 , 29 , 31 , 32 , 34 , 35 , 36 , 40 , 41 , 44 , 45 , 47 , 50 , 51 , 52 , 53 , 55 , 59 , 61 , 63 ]…”
Section: Serum Mirnas As Clinical Potential Biomarkers For Human Ostementioning
confidence: 99%
“…MicroRNAs (miRNAs) naturally exist in a variety of living organisms, acting as a crucial element in gene modulation through binding to a specific region in open reading frames (ORFs) or untranslated regions (UTRs), blocking the translation process either by degrading or blocking the mRNA and leading to a knock down or through suppression of downstream processes 9 - 11 . It has been reported that overexpression of miR-29a can result in myocardial injury 12 .…”
Section: Introductionmentioning
confidence: 99%